Role of Age-Related Shifts in Rumen Bacteria and Methanogens in Methane Production in Cattle - Liu, Chong; Meng, Qinghui; Chen, Yongxing; Xu, Mengsi; Shen, Min; Gao, Rui; Gan, Shangquan (Frontiers in Microbiology, 2017)
Rumen microbiota are essential for maintaining digestive and metabolic functions, producing methane as a byproduct. Dairy heifers produce large amounts of methane based on fermentation of digested organic matter, with adverse consequences for feed efficiency and the environment. It is therefore important to understand the influence of host age on the relationship between microbiota and methane production. This study explored the age effect on the relationship between microbial communities and enteric methane production in dairy cows and heifers using high-throughput sequencing. Methane production and volatile fatty acid (VFA) concentrations were age-related. Heifers (9-10 months) had lower methane production but higher methane production per dry matter intake (DMI). The acetate:propionate ratio decreased significantly with increasing age. Age-related microbiota changes in the rumen were reflected by a significant shift in bacterial taxa, but relatively stable archaeal taxa. Prevotella, Ruminococcus, Flavonifractor, Succinivibrio, and Methanobrevibacter were affected by age. This study revealed different associations between predominant bacterial phylotypes and Methanobrevibacter with increasing age. Prevotella was strongly correlated with Methanobrevibacter in heifers; howerver, in older cows (96-120 months) this association was replaced by a correlation between Succinivibrio and Methanobrevibacter. This shift may account for the age-related difference in rumen fermentation and methane production per DMI.